Efficacy of microbial inoculants and organic fertilizer for establishing large cardamom (Amomum subulatum Roxb.) sucker nursery - J Thomas, T N Deka, S S Mahesh, K A Saju, B A Vadiraj, (Journal of Spices and Aromatic Crops, 2014)
An experiment was conducted to evaluate the effectiveness of various microbial inoculants on large cardamom suckers. The study demonstrated the beneficial effect of microbial inoculants, viz., Azospirillum, Pseudomonas fluorescens, Trichoderma harzianum, phosphate solubilizing bacteria (PSB) and Arbuscular Mycorrhizal Fungi (AMF) on plant growth. Application of farm yard manure (FYM) + Azospirillum + P. fluorescens + T. harzianum + AMF recorded significantly higher number of tillers and plant height as compared to other treatments. Hence, using the above microbial inoculants may facilitate better establishment and growth for planting material in the nursey.